Pergeseran Peran Qawwam Akibat Kemandirian Ekonomi Perempuan: Analisis Sosio-fiqh atas Determinan Perceraian - Zuhairiah; Nur Aulia Rahmah; St. Mukhlisshah (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study analyzes the implications of women’s economic independence on the reinterpretation of qawwam and its relation to the increasing trend of female-initiated divorce (cerai gugat) in contemporary Muslim families. Using a qualitative socio-fiqh approach, the research combines normative Islamic legal analysis with secondary empirical data, including official divorce statistics from the Religious Courts and the Central Bureau of Statistics (BPS), as well as selected public divorce cases as illustrative contexts. The findings indicate that women’s economic independence does not function as a direct cause of divorce, but as an enabling factor that reshapes power relations and decision-making dynamics within marriage. This condition encourages a shift in the understanding of qawwam from a hierarchical, maintenance-based authority toward a functional and partnership-oriented leadership model. From a maqāṣid al-syarī‘ah perspective, cerai gugat can be understood as a legitimate corrective mechanism to prevent harm and uphold justice and human dignity. This study contributes to contemporary Islamic family law discourse by offering a contextual reinterpretation of qawwam that is responsive to socio-economic change while remaining grounded in the objectives of Islamic law.